Challenges and recent developments on nanoparticle-reinforced metal matrix composites - Basak, A.; Pramanik, Alokesh; Islam, Mohammad Nazrul; Anandakrishnan, V. (Elsevier Ltd, 2015)
The quest for advanced functional materials with superior functionality is being driven in various frontiers of engineering materials. One such frontier is the research of metal matrix composites (MMCs), which has already been proven as one of the most productive fields. With advance technology, it is possible to reinforce the MMCs with nanosized particles compared with conventional micron-sized counterparts. However, the addition of nanoparticles to MMCs to improve their mechanical properties is not unconditional, and there are several factors that should be taken into consideration. This present chapter gives an overview of such considerations along with recent trends in this field.